PENERAPAN MODEL COMPLETE SENTENCE PADA MATERI MAKANAN SEHAT DAN BERGIZI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV MIN 42 PIDIE - Nia Wardhani (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2019)
The aim of the study iwas to find out if Complete Sentence Model could improve learning outcomes of fourth grade students’ of MIN 42 Pidi. The research was carried out in two cycles. The procedures consisted of planning, acting, observing and reflecting. The subject of the research was the fourth grade students, they were 19 students totally which are 7 males and 12 females. The result showed the average and classical achievement: cycle I are 68.1 and 42%; cycle II are 89.2 and 100%. Thus, Complete Sentence Model can improve the students’ learning outcomes.